Augmentation versus No Augmentation for Immediate Postextraction Implants - Huda Hamed Basher Mohamed; Asma M. Serag Eldien; Amr Zahran (International Journal of Dentistry)
Purpose. To assess the effects of augmentation versus no augmentation in patients restored with immediate postextraction single-tooth implants on implant failure and patient satisfaction. Materials and methods. We searched the Cochrane Oral Health Group Trial Register, Cochrane Central Register of Controlled Trials, MEDLINE, and the WHO International Clinical Trial Registry Platform (22 March 2017). Two reviewers independently assessed trials for inclusion and risk of bias, extracted data, and checked for accuracy. We have expressed results as risk ratio or mean differences, together with their 95% confidence intervals. Results. We included six studies (287 participants). Two trials compared no augmentation versus bone graft augmentation and reported no implant failures in both groups after a follow-up period of 6 months (20 implants) and 1 year (34 implants). One trial compared bone graft augmentation versus membrane augmentation and reported no difference in implant failure between both groups after 6 months (risk ratio (RR) 0.98, 95% confidence interval (CI) 0.06 to 15.31) or 1 year of follow-up (RR 0.33, 95% CI 0.01 to 7.86), and no implants were lost after 3 years. Three trials compared membrane augmentation versus combined bone graft and membrane augmentation, and there was no difference between the groups after six months of follow-up in implant failure (RR 5.13, 95% CI 0.63 to 41.93) or after 1 year (RR 0.38, 95% CI 0.02 to 9.05). There was insufficient evidence regarding patient satisfaction in all the included trials. Conclusions. In patients restored with immediate postextraction single-tooth implants, there is insufficient evidence to recommend simultaneous augmentation or a certain augmentation protocol to enhance implant survival and patient satisfaction. This trial is registered with PROSPERO (CRD42017054439).